Furnace shell and rolling ring assembly structure of Kaldor furnace - CAO KEFEI; LI WEIZHOU; ZHANG BO; MA YUTIAN; TANG HONGCAI; AN GUORUI; ZHANG ZHENMIN; GU KEYOU; FENG XIAOMEI (2012)
The utility model relates to improvement on a furnace shell and rolling ring assembly structure of a Kaldor furnace. The structure comprises a rolling ring, a furnace shell, an elastic disc spring and a connecting bolt and is characterized in that: (1) a concave base line which is provided with a groove and arranged at the inner side of the rolling ring upwards extends from the middle part, and structures of a same plane, a transition inclined plane and a vertical face are formed at the inner side of the groove; (2) a structure of the furnace shell, which is connected with the rolling ring, is matched with a structure which is provided with the groove and arranged at the inner side of the rolling ring, and the transition inclined plane is arranged at a contact top angle; and (3) the connecting bolt passes through the structure of the furnace shell, which is connected with the rolling ring, and the rolling ring, and the elastic disc spring is arranged at a set screw. In the structure, concave-convex groove mat